Z żałobnej karty. Wspomnienie o Profesorze Józefie Nowakowskim - Uliasz, Stanisław (Tematy i Konteksty, 2014)
The text is a tribute to Professor Józef Nowakowski, who died in 2014. He was a long-time scholar in the Institute of Polish Philology at the Pedagogical University in Rzeszów, researcher into 20th century poetry, popular literature, the noble traditions in Polish culture as well as the history of the Home Army in the region of Strzyżów.